Analisis Kebutuhan Air Irigasi dan Ketersediaan Sumber Daya Air Berbasis Sistem Informasi Geografis di Kecamatan Krui Selatan Kabupaten Pesisir Barat - Jayanegara, Hanissa I; Ridwan, Ridwan; Amin, Muhammad; Asmara, Sandi (Jurnal Agricultural Biosystem Engineering, 2024)
Krui Selatan Subdistrict has potential in the productivity of rice and other food crops such as corns and soybeans. However, the management of water resources available to meet water needs in agriculture has not been optimal. This study aims to determine the potential amount of water resources for food crops (rice and palawija), to obtain the optimal planting area based on the potential of available water resources and to determine the cropping pattern of food crops according to the potential of available water resources. The analysis of research carried out in this study includes land water balance, crop water needs, irrigation water needs, water resource potential and water resource adequacy. This study uses a Geographic Information System (GIS) equipped with a SWAT (Soil and Water Assessment Tools) model approach during the research process. Potential water resources available in Krui Selatan Subdistrict can be utilized for land development with rice and secondary crops. The intensity of rice planting is carried out 2 (two) times a year with a rice planting area that can be developed of 72,15 ha. Meanwhile, the development of palawija, which this study uses soybeans, can be carried out in planting season III with a rice field area that can be used for crops soybean 54,11 ha. Keywords:  Irrigation, Geographic Information System, Water Resources.